IMPLEMENTASI PERATURAN PRESIDEN NOMOR 70 TAHUN 2012 TENTANG PENGADAAN BARANG / LAYANAN OLEH UNIT ELEKTRONIK (E-PENGADAAN) PADA LAYANAN PENGADAAN (ULP) UNIVERSITAS LAMPUNG - Ngadiman Ngadiman (P3M STISIPOL Dharma Wacana Metro, 2018)
This study aims to see the implementation of policies and constraints on communication process, resources, disposition and bureaucratic structure in the implementation of the procurement of goods/services based on electronic (eprocurement). This research used descriptive method with qualitative approach. Data was collected through in-depth interview study, documentation and observation, while the technique of the validity of data was done through triangulation, including triangulation methods, data sources and the data itself.The results of this study showed that e-procurement have demonstrated their success, although it hasn't been optimal, which gained efficiency and effectiveness on a number of indicators. From the aspect of time, the procurement process with e-procurement system proved faster because it only takes 14-18 working days, the conventional system takes more than 30 days' work through e-procurement can reduce the potential for corrupt practices, for a meeting between the auction committee and the auction participants islimited a lot. At the time of the auction is still widely practiced in the conventional direct meetings between the auction partipants and the auction committee which has opened the chance of occuring